2011
DOI: 10.1080/14634988.2011.624863
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mercury concentrations and loads from four western Lake Superior watersheds using continuous in-stream turbidity monitoring

Abstract: Many streams along the Minnesota coast of Lake Superior have been listed as impaired from either high turbidity or high fish mercury concentrations or both. Both turbidity and total mercury have been shown to be strongly correlated to total suspended sediment in many disturbed watersheds. Turbidity and total mercury concentrations and loads were estimated in four western Lake Superior watersheds from 2005-2006 using automated in-stream turbidity measurements. Regression models were developed relating this near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Continuous, short time interval pollutant concentrations were estimated using these pollutant-specific regressions with turbidity and then combined with the discharge data to derive "instantaneous" loads which were then summed to any longer time interval desired (storm, monthly, or annual). The TSR estimator has been discussed previously and found to work well for computing loads of suspended sediments and mercury for urbanized and mixed land use systems (e.g., Lewis, 1996;Quémerais et al, 1999;Wall et al, 2005;David et al, 2009;Ruzycki et al, 2011;Riscassi and Scanlon, 2013). Expanding upon what has been learned from previous authors, we show here that turbidity can form strong and significant correlations with many trace organic compounds and the TSR method is viable for loads estimation of particle-associated organic pollutants.…”
Section: Quantifying Mean Concentrations and Loadsmentioning
confidence: 69%
“…Continuous, short time interval pollutant concentrations were estimated using these pollutant-specific regressions with turbidity and then combined with the discharge data to derive "instantaneous" loads which were then summed to any longer time interval desired (storm, monthly, or annual). The TSR estimator has been discussed previously and found to work well for computing loads of suspended sediments and mercury for urbanized and mixed land use systems (e.g., Lewis, 1996;Quémerais et al, 1999;Wall et al, 2005;David et al, 2009;Ruzycki et al, 2011;Riscassi and Scanlon, 2013). Expanding upon what has been learned from previous authors, we show here that turbidity can form strong and significant correlations with many trace organic compounds and the TSR method is viable for loads estimation of particle-associated organic pollutants.…”
Section: Quantifying Mean Concentrations and Loadsmentioning
confidence: 69%
“…Considering this, and the results from other western Lake Superior basin streams (e.g. Ruzycki, 2011Ruzycki, , 2014Detenbeck et al, 2003Detenbeck et al, , 2005Anderson et al, 2003), it appears to be more appropriate to use storm events to investigate the relationship of sediment related parameters to landscape/land use while base flow may be more appropriate for dissolved and physical parameters.…”
Section: Hydrologic Regimesmentioning
confidence: 92%
“…Ruzycki et al (2011Ruzycki et al ( , 2014 investigated the effects of flow and hydrologic regime on sediment related parameters -TSS, T, and TP -in four streams that drained into either the St. Louis River Estuary or the western arm of Lake Superior within 10 km of the estuary. They found that sediment related parameters varied strongly with hydrologic regime and discharge and that there were significant differences between streams that were near each other.…”
Section: Hydrologic Regimesmentioning
confidence: 99%
“…Several manufacturers have developed self-cleaning sensors with low power requirements that are purported to allow for long-term in situ deployments. A number of researchers have assessed the use of continuous, instream turbidity as a surrogate for total suspended solids (TSS) and/or suspended sediment concentration (SSC) (Gippel, 1989;Lewis, 1996;Packman et al, 1999;Christensen, 2001;Dana et al, 2004;Jastram et al, 2007;Stubblefield et al, 2007;Jastrum et al, 2010;Jones et al, 2010;Williamson and Crawford, 2011), total phosphorus (TP) (Stubblefield et al, 2007;Jones et al, 2010), fecal coliforms (Christensen et al, 2000), and total mercury (Balogh, 1997;Ruzycki et al, 2011). Christensen (2001) used instream measures of specific electrical conductivity (EC at 25°C), pH, temperature, turbidity, and dissolved oxygen to estimate total dissolved solids, sodium, chloride, fecal coliforms, as well as suspended sediment.…”
Section: Introductionmentioning
confidence: 99%